An experimental study of accelerated mineral carbonation of industrial waste red gypsum for CO2 sequestration. Issue 35 (January 2020) - Rahmani, Omeid
Highlights: Red gypsum is an industrial waste rich in calcium favored for CO2 sequestration. Mono-ethanolamine absorbed more CO2 in the aqueous solution rich in calcium ions. Proposed accelerated carbonation consumed lower energy while forming calcite. Abstract: This study provides a novel approach to sequester carbon dioxide (CO2 ) using industrial waste red gypsum (RG) in an accelerated mineral carbonation process. In this study, RG samples and products were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), and transmission electron microscope (TEM). The XRD analysis of RG revealed that two main constitutions of RG are gypsum (CaSO4 .2H2 O) and hematite (Fe2 O3 ). From XRF analysis, RG samples consisted of calcium oxide (CaO), sulfur trioxide (SO3 ), and ferric oxide (Fe2 O3 ) as major components and titanium dioxide (TiO2 ), manganese oxide (MnO), and europium oxide (Eu2 O3 ) as minor components. The accelerated mineral carbonation of RG was first performed using different concentrations of sulfuric acid (H2 SO4 ) from 0.5 M to 2 M to extract the calcium ions from the RG. Then, the mineral carbonation process was performed within an Autoclave mini reactor by preparing an aqueous solution containing RG, CO2, and 5 wt% 0.1 M to 1.4 M mono-ethanolamine (MEA). The results showed that using 1.4 M MEA could absorb the highest amount of CO2 to precipitate the calcite. The significant advantages of using MEA were related to the further absorption of CO2 than 2 M H2 SO4 in the slurry and the lower consumption of energy to precipitate the calcite. The findings presented in this study shed new light on precipitating carbonate minerals like calcite from industrial wastes rich in calcium as well as ones rich in iron, barium, and magnesium.